Self-efficacy to entrepreneurship intention: Role of entrepreneurial passion and role models - Doan Thi Thanh, Thuy; Viet, Le Hoai (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
This study investigates the effects of self-efficacy, entrepreneurial passion, and role models on entrepreneurship intention. The research is conducted through a survey method and multivariate data analysis. Students at a number of universities in Vietnam were sent questionnaires to complete in order to gather data. 446 valid sample data were assessed using a structural equation model. The findings show that: entrepreneurship intention is positively influenced by self-efficacy; self-efficacy positively affects entrepreneurial passion; entrepreneurial passion strongly influences entrepreneurship intention; entrepreneurial passion mediates the relationship between self-efficacy and entrepreneurship intention; role models act as a moderator in the relationship between entrepreneurial passion and entrepreneurship intention. The study suggests measures that universities can create in specific contexts and cultures to support the business activities of university students. This will add positive energy for students to enter the entrepreneurial path as well as nurture creative talents Further research is encouraged using a longitudinal design to examine the determinants of entrepreneurship intention at two or more different points in time.